TRAGIC LOSS OR GOOD RIDDANCE? THE IMPENDING DEMISE OF TRADITIONAL SCHOLARLY JOURNALS - Odlyzko, Andrew (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1994)
Refering particuliarly to mathematics and the natural sciences, the author argues that the potential of electronic technology renders traditional publishing superfluous.